Noise and vehicular traffic on the main roads of Tacna city during the COVID 19 pandemic - Almanza Quispe, Williams Sergio (2022)
Vehicular traffic has increased in much of the world in recent times, and everything indicates that it will continue to worsen, constituting a danger to the quality of urban life. The strong negative impacts, both immediate and long-term, require multidisciplinary efforts to keep it under control through the design of appropriate policies and measures. For this reason, the noise generated in the main roads of the city of Tacna was analyzed in order to know if under movement restrictions due to the health situation generated by COVID-19 that the government implemented, the pressure levels were reduced by the decrease in vehicular traffic. For this purpose, 67 sampling points during daytime hours, and 30 points for nighttime hours were established by convenience on different roads in the city of Tacna. A Type I integrating sound level meter was used, certified by the National Quality Institute (INACAL), which measures the equivalent continuous sound level (LAeq). The resulting values were contrasted with the Environmental Quality Standards (ECA) for noise (D.S. No. 085 -2003-PCM). No significant correlation was found between noise with vehicular traffic and the type of area during daytime hours, only a correlation was found between noise and type of area (Spearman's Rho = -0.447 and p-value= 0.013). It is concluded that noise levels in times of pandemic remained at levels similar to periods without the pandemic, so the vehicular restrictions imposed by the government did not influence on the reduction of noise to adequate levels; on the contrary, they exceeded what was established by the regulations in most areas.